Indigenous Ancestry and Admixture in the Uruguayan Population - Spangenberg, Lucía; Fariello, María Inés; Arce, Darío; Illanes, Gabriel; Greif, Gonzalo; Shin, Jong-Yeon; Yoo, Seong-Keun; Seo, Jeong-Sun; Robello, Carlos; Kim, Changhoon; Novembre, John; Sans, Mónica; et al. (Frontiers in Genetics, 2021)
The Amerindian group known as the Charrúas inhabited Uruguay at the timing of European colonial contact. Even though they were extinguished as an ethnic group as a result of a genocide, Charrúan heritage is part of the Uruguayan identity both culturally and genetically. While mitochondrial DNA studies have shown evidence of Amerindian ancestry in living Uruguayans, here we undertake whole-genome sequencing of 10 Uruguayan individuals with Charruan heritage. We detect chromosomal segments of Amerindian ancestry supporting the presence of indigenous genetic ancestry in living descendants. Specific haplotypes were found to be enriched in 'Charrúas' and rare in the rest of the Amerindian groups studied. Some of these we interpret as the result of positive selection, as we identified selection signatures and they were located mostly within genes related to the infectivity of specific viruses. Historical records describe contacts of the Charrúas with other Amerindians, such as Guaraní, and patterns of genomic similarity observed here concur with genomic similarity between these groups. Less expected, we found a high genomic similarity of the Charrúas to Diaguita from Argentinian and Chile, which could be explained by geographically proximity. Finally, by fitting admixture models of Amerindian and European ancestry for the Uruguayan population, we were able to estimate the timing of the first pulse of admixture between European and Uruguayan indigenous peoples in 1658 and the second migration pulse in 1683. Both dates roughly concurring with the Franciscan missions in 1662 and the foundation of the city of Colonia in 1680 by the Spanish.